Left ventricular thrombosis following apical myocardial infarction: may CMR strain analysis tell us something?. (13th July 2021) - Brunetti, G; Cardaioli, F; De Lazzari, M; Cipriani, A; Cecere, AG; Cecchetto, A; Baritussio, A; Giorgi, B; Motta, R; De Conti, G; Tarantini, G; Cacciavillani, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left ventricular thrombosis (LVT) is a possible complication following myocardial infarction (MI). Besides infarct size, risk factors for LVT include ST-elevated MI (STEMI), anterior and apical location, reduced left ventricular ejection fraction (LVEF) and the presence of microvascular obstruction. Echocardiography quantified myocardial strain has been associated with LVT following MI. Recently, global longitudinal strain, calculated with feature tracking (FT) - CMR, emerged as an independent predictor of major cardiovascular events following MI. Anyway, the relationship between abnormalities on FT-CMR and LVT following MI is still unexplored. Aim of our study is to investigate the possible association between abnormal strain on FT-CMR and LVT following apical STEMI. Methods: We performed a retrospective analysis including all patients with a previous apical STEMI, who underwent CMR at our Institute between August 2013 and October 2020. Patients with ongoing anticoagulant therapy were excluded. Differences in global and segmental strain on CMR between patients with and without LVT were tested in a propensity-matched sample, using LVEF, age, gender, time from MI diagnosis and number of LV segments with transmural late gadolinium enhancement (LGE) as covariates to assign propensity score. Furthermore, difference in terms of apical to global radial strain percentual deviation (AGD), calculated as [(Global Radial Strain – Apical Radial Strain)/Global Radial Strain] * 100, was tested. Results: Of 356 patients with apical STEMI undergoing CMR at our center, 37 (10.4%) were diagnosed with LVT. After performing a propensity score matching, we obtained a sample of 36 pairs, with a mean age of 65 (SD 11) years, and a median EF of 35% (IQR 27-42); 59 (82%) of them were male. A significant difference in terms of apical radial strain was found between the two groups, with a median strain of 10.75 (IQR 6.8–16.5) in patients without LVT compared to a value of 5.25 (IQR 2.7–9-6) in patients with LVT (p = 0.007). No differences were found in terms of global longitudinal, radial and circumferential strain (p = 0.19, p= 0.2 and p= 0.49 respectively) and segmental circumferential and longitudinal strain. When considering the AGD parameter, a significant difference was found between the two groups, with a median deviation of 12% (IQR -20; +48) in patients without LVT and 51% (IQR +47; +75) in patients with LVT (p= 0.0003). Furthermore, an AGD value of 26% was found to be the most accurate in terms of sensitivity and specificity applying a Receiver Operating Characteristic (ROC) curve analysis (AUC 0.74; CI 0.62-0.85). Conclusions: Among patients with transmural MI involving LV apex, reduced apical radial strain on FT-CMR is associated with the presence of LV thrombosis. Furthermore, among patients developing LV thrombi, a greater apical radial strain deviation from the global one was found, with a threshold value of 26% at ROC curve analysis.